The CRP/MLP/TLP family of LIM domain proteins: acting by connecting. - Weiskirchen, R.; Gunther, K. (BioEssays, 2003)
In vertebrates, members of the cysteine-rich protein (CRP) family are characterized by the presence of two LIM domains linked to short glycine-rich repeats. These proteins mediate protein-protein interactions and are of fundamental importance for cell differentiation, cytoskeletal remodeling, and transcriptional regulation. To date, a vast amount of information about vertebrate CRPs has become available, including their biological functions, interacting partners, and three-dimensional structures. Compatible with a molecular adapter role, structural data reveal that the LIM domains within these proteins represent completely independent folded units bridged by flexible linker regions. The physiological roles for individual CRPs was determined by targeted gene disruption analysis and by identification of common and specific binding partners by means of yeast and mammalian two-hybrid screens. Several CRP-like LIM domain proteins with close structural and sequence similarity were identified in arthropods, protozoas and plants, supporting the notion that this subset of LIM domain proteins has been highly conserved over the span of evolution thereby emphasizing the importance of their function.